PEMBATASAN UPAYA HUKUM PERKARA PERDATA GUNA MEWUJUDKAN ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA RINGAN - Bambang Sugeng Ariadi S; Johan Wahyudi; Razky Akbar (Universitas Airlangga, 2015)
The most important thing for any regulation judicial principle is simple, fast and low cost is to reduce the accumulation of cases in the Supreme Court. That is because, line with the increasing increasing number of incoming cases, and also that successfully terminated in the District Court and Court of Appeal, then the incoming number of decisions in the Supreme Court also increased and began to be a serious problem. In this regard, People's Consultative Assembly (MPR) seriously consider this and responded by provisions, that is TAP MPR No. VIII/MPR/2000 about of the Annual Report of State High Institutions at the Annual Session of the People's Consultative Assembly of the Republic of Indonesia in 2000 which one substance recommend that the Supreme Court immediately resolve pending lawsuits by increasing the number and quality of decisions and that the Supreme Court makes the rules o restrict the entry of cassation cases. Following up on the existence of the MPR decrees, he Supreme Court has issued several provisions n order to limit legal action in order to realize judicial principle is simple, fast and low cost, either in the form of the Supreme Court Rules (Perma) nor Supreme Court Circular Letter (Sema). This article is useful for know and understand how much has been the implementation judicial principle is simple, fast and low cost, in order to reduce the buildup of civil cases.